New Concept of the Biosynthesis of 4-Alkyl-L-Proline Precursors of Lincomycin, Hormaomycin, and Pyrrolobenzodiazepines: Could a γ-Glutamyltransferase Cleave the C–C Bond? - Jiraskova, Petra; Gazak, Radek; Kamenik, Zdenek; Steiningerova, Lucie; Najmanova, Lucie; Kadlcik, Stanislav; Novotna, Jitka; Kuzma, Marek; Janata, Jiri (Frontiers in Microbiology, 2016)
Structurally different and functionally diverse natural compounds – antitumour agents pyrrolo[1,4]benzodiazepines, bacterial hormone hormaomycin, and lincosamide antibiotic lincomycin – share a common building unit, 4-alkyl-L-proline derivative (APD). APDs arise from L-tyrosine through a special biosynthetic pathway. Its generally accepted scheme, however, did not comply with current state of knowledge. Based on gene inactivation experiments and in vitro functional tests with recombinant enzymes, we designed a new APD biosynthetic scheme for the model of lincomycin biosynthesis. In the new scheme at least one characteristic in each of five final biosynthetic steps has been changed: the order of reactions, assignment of enzymes and/or reaction mechanisms. First, we demonstrate that LmbW methylates a different substrate than previously assumed. Second, we propose a unique reaction mechanism for the next step, in which a putative γ-glutamyltransferase LmbA indirectly cleaves off the oxalyl residue by transient attachment of glutamate to LmbW product. This unprecedented mechanism would represent the first example of the C–C bond cleavage catalyzed by a γ-glutamyltransferase, i.e., an enzyme that appears unsuitable for such activity. Finally, the inactivation experiments show that LmbX is an isomerase indicating that it transforms its substrate into a compound suitable for reduction by LmbY, thereby facilitating its subsequent complete conversion to APD 4-propyl-L-proline. Elucidation of the APD biosynthesis has long time resisted mainly due to the apparent absence of relevant C–C bond cleaving enzymatic activity. Our proposal aims to unblock this situation not only for lincomycin biosynthesis, but generally for all above mentioned groups of bioactive natural products with biotechnological potential.